Cover Feature: Impact of Pore Size and Defects on the Selective Adsorption of Acetylene in Alkyne‐Functionalized Nickel(II)‐Pyrazolate‐Based MOFs (Chem. Eur. J. 46/2021). Issue 46 (22nd July 2021) - Afshariazar, Farzaneh; Morsali, Ali; Sorbara, Simona; Padial, Natalia M.; Roldan‐Molina, Esther; Oltra, J. Enrique; Colombo, Valentina; Navarro, Jorge A. R.
Abstract : As a consequence of specific interactions between acetylene molecules and alkyne, aromatic and hydroxide residues of metal clusters, two isoreticular nickel(II) pyrazolate‐based metal–organic frameworks bearing alkyne moieties on the ligand backbones are suitable for the selective separation of the challenging acetylene over CO2 gas mixture. Moreover, a post‐synthetic treatment of these materials with ethanolic KOH solution gives rise to linker vacancy defects and the incorporation of extra‐framework potassium ions, which are responsible for a further modulation of the interactions with the adsorbate molecules. More information can be found in the Full Paper by J. A. R. Navarro et al. (DOI: 10.1002/chem.202100821 ).